The Impact of Destination Service Quality and Destination Environment on Tourist Satisfaction: A Field Study on Jordans Golden Triangle for Tourists Point of View - Bader, Feras Mohammad; Hasoneh, Abdelbaset; Afaneh, Saeda; Khanfar, Salim M (Journal of Tourism Management Research, 2018)
The aim of this study was to explore the impact of service quality and destination environment on tourist satisfaction in Jordan’s Golden Triangle (Aqaba, Petra and Wadi Rum). A descriptive survey method was adopted in order to conduct the study. A questionnaire-based survey was developed on the basis of literature review and previous studies. Once validity and reliability of the questionnaire established, it was self-administered to a sample comprised 600 foreign tourists visiting the study area. Out of the distributed questionnaires, 374 were returned valid for statistical analysis purpose (response rate = 62.3%). The study underlined a statistically significant impact of service quality as well as its dimensions on tourist satisfaction and a statistically significant impact of destination environment and its dimensions on tourist satisfaction. In relation to differences among tourists in terms of their responses, the results pointed out that there were no statistically significant differences in tourists’ responses in favor of their personal data, except companionship.